SMART POLITICAL MOVEMENT: BUILDING POLITICAL LITERACY WITH Z GENERATION PARTICIPATION IN THE 2024 ELECTIONS - Septian, Esa; Wulandari, Septi (Masyarakat Indonesia, 2024)
This study aims to determine Generation Z's political participation in building political literacy in the 2024 General Election in Bojonegoro Regency. The research method uses qualitative research with a case study approach. Data collection uses interviews, observation, and documentation methods. The informants of this research were the General Election Commission, the Election Supervisory Board, and students as Gen Z. The data were analyzed through data reduction, data presentation, and data analysis. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that Generation Z's political participation in improving political literacy through social media by realizing elections with integrity and quality. Students' initiative level has a critical mindset, and technological literacy is an asset in improving political literacy in deflecting negative issues circulating. The intensity of Gen Z in politics through social media as a forum in encouraging freedom of opinion and creativity.